Tren Penelitian Kesehatan Mental Siswa Berbasis Nilai Islam di Indonesia: Systematic Literature Review - Kamarulzaman (Lembaga Anotero Scientific Pekanbaru, 2025)
The mental health of students in Indonesia faces complex challenges due to academic, social pressures and post-pandemic impacts. Although Islamic values ​​such as patience, gratitude and trust are believed to be able to strengthen students' psychological resilience, there has been no systematic consolidation reviewing the effectiveness of these interventions. This research aims to conduct a Systematic Literature Review (SLR) of studies on student mental health based on Islamic values ​​in Indonesia for the 2013–2023 period. The SLR method follows the PRISMA 2020 and Kitchenham & Charters (2022) guidelines through four stages: identification, screening, eligibility, and inclusion. The results showed that 68 articles met the inclusion criteria, with a significant increasing trend post-2020. The dominant interventions in the form of Sufistic counseling, Al-Qur'an therapy, and Islamic character education have proven to be effective in improving students' psychological well-being. However, there are still methodological gaps and a lack of longitudinal research. This study emphasizes the need for standardization of methodology and integration of Islamic psychology in national education policy.